Integration analysis of lncRNA and mRNA expression data identifies DOCK4 as a potential biomarker for elderly osteoporosis - Chengai Wu; Chao Wang; Bin Xiao; Shan Li; Yueyang Sheng; Qianqian Wang; Jianfeng Tao; Yanzhuo Zhang; Xu Jiang (BMC, 2024)
Abstract Background We aimed to identify some potential biomarkers for elderly osteoporosis (OP) by integral analysis of lncRNA and mRNA expression data. Methods A total of 8 OP cases and 5 healthy participants were included in the study. Fasting peripheral venous blood samples were collected from individuals, and total RNA was extracted. RNA-seq library was prepared and sequenced on the Illumina HiSeq platform. Differential gene expression analysis was performed using "DESeq2" package in R language. Functional enrichment analysis was conducted using the "clusterProfiler" package, and the cis- and trans-regulatory relationships between lncRNA and target mRNA were analyzed by the lncTar software. A protein-protein interaction (PPI) network was constructed using the STRING database, and hub genes were identified through the MCODE plugin in Cytoscape. Results We identified 897 differentially expressed lncRNAs (DELs) and 1366 differentially expressed genes (DEGs) between normal and OP samples. After co-expression network analysis and cis-trans regulatory genes analysis, we identified 69 candidate genes regulated by lncRNAs. Then we further screened 7 genes after PPI analysis. The target gene DOCK4, trans-regulated by two lncRNAs, was found to be significantly upregulated in OP samples. Additionally, 4 miRNAs were identified as potential regulators of DOCK4. The potential diagnostic value of DOCK4 and its two trans-regulatory lncRNAs was supported by ROC analysis, indicating their potential as biomarkers for OP. Conclusion DOCK4 is a potential biomarker for elderly osteoporosis diagnostic. It is identified to be regulated by two lncRNAs and four miRNAs.